El Código Orgánico Integral Penal y su repercusión en relación a la prevención de la violencia intrafamiliar en los juzgados de la familia, mujer, niñez y adolescencia de Guayaquil - Erazo Llerena, Edgar Alexander (2022)
Domestic violence is a structural problem at the national and international level, where the victim suffers all kinds of discrimination, aggression, harassment and degradation; in the face of this outrage, the laws related to punishment in this area have not diminished the consequences of this social phenomenon, leading to the conclusion that there is a lack of preventive policy. The present work contributes new elements that contribute to implement systems oriented to guarantee, in a personal and effective way, the protection of the elementary rights of the victims, not only from the punitive point of view, but from a preventive, human and more committed scope, considering the penal norm, as a constitutional principle of ultimate ratio, principle that is contemplated in Art. 3 of our penal legal normative (COIP).............